ANALYSIS OF ENGLISH LANGUAGE SKILLS OF MATHEMATICS EDUCATION STUDENTS: DETERMINING FACTORS AND SOLUTIONS - Swasti Maharani; Widia Yunita (LPPM Universitas Bina Bangsa, 2023)
This study aims to analyze the determinants of English skills of Mathematics Education students and identify solutions that can improve them. The research method used was qualitative by involving prospective mathematics teacher students from one of the universities in the city of Madiun. Data collection instruments include questionnaires, interviews, and TOEFL tests. The results showed that factors such as previous educational background, learning motivation, exposure to English, and learning methods affected students' English skills. Lack of motivation to learn English and inadequate level of English skills are the main obstacles faced by students. Few students reach the adequate TOEFL test threshold. Limitations of this study include limited samples, data collection methods that can create bias, the specific context of Mathematics Education, time constraints, and other possible factors that are not taken into account. Awareness of these limitations is important in interpreting research results and formulating appropriate recommendations to improve the English skills of Mathematics Education students